2020
DOI: 10.1007/s11187-020-00317-z
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs’ age, institutions, and social value creation goals: A multi-country study

Abstract: This study explores the relationship between an entrepreneur's age and his/her social value creation goals. Building on the lifespan developmental psychology literature and institutional theory, we hypothesize a U-shaped relationship between entrepreneurs' age and their choice to create social value through their ventures, such that younger and older entrepreneurs create more social value with their businesses while middle age entrepreneurs are relatively more economically and less socially oriented with their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 104 publications
2
52
0
9
Order By: Relevance
“…This is consistent with the analysis of overoptimism (cf. Brieger, Bäro, Criaco, & Terjesen, 2020;Cieślik, Kaciak, & van Stel, 2018), in which young people see more favorable conditions for seizing available opportunities in the market. Contrary to this result, entrepreneurial behavior among students seems to be very low.…”
Section: Empirical Strategy and Estimation Methodsmentioning
confidence: 99%
“…This is consistent with the analysis of overoptimism (cf. Brieger, Bäro, Criaco, & Terjesen, 2020;Cieślik, Kaciak, & van Stel, 2018), in which young people see more favorable conditions for seizing available opportunities in the market. Contrary to this result, entrepreneurial behavior among students seems to be very low.…”
Section: Empirical Strategy and Estimation Methodsmentioning
confidence: 99%
“…The behavior of focus in this chapter is entrepreneurial activity. A team of researchers [7] assert citing the body of research, "Individuals' orientation toward entrepreneurial activities differs depending on where they stand in their lifespans (p. 1)."…”
Section: Theoretical Frame: Developmental Perspectivementioning
confidence: 99%
“…Past research has shown an inverted U-shaped relationship between age and entrepreneurship [7]. It has also been argued that there is a negative relationship between age and engaging in entrepreneurship [11,23].…”
Section: Brief Literature Review: Age and Entrepreneurshipmentioning
confidence: 99%
See 2 more Smart Citations